The Influence of SAVI Learning Model on Student Learning Outcomes in Learning National Mandatory Song Learning SMP Parulian 2 Medan - Pita H.D Silitonga; Theodora Sinaga; Noralisa Noralisa (BIRCU, 2019)
This study aims to determine the effect of learning model SAVI (Somatic Audiotori, Visual, Intellectual Property) to the learning outcomes of students class VII SMP Parulian 2 Medan.This study is based on a theoretical foundation to explain the learning model SAVI, learning outcomes, and Song local area, along with the hypothesis. The research method in this study using an experimental research. This type of research is True Experimental Design with pretest design -Posttest Control Group Design. The population in the study were all students of class VII SMP Parulian 2 field consisting of 4 classes. Sampling was done by random sampling by taking two classes, namely the class VII4 as an experimental class that numbered 30 people and VII2 class as the control class that numbered 30 people. The instrument used to determine student learning outcomes is the achievement test in the form of multiple choice numbered 30 and 20 items that have been declared valid for the experimental class and control class that has been tested on VII1 class in junior Parulian 2 Medan.The second class are given a pretest to determine the ability of the student before the beginning of the treatment given in each grade, with an average value of 38.83 experimental class and control class 35.83. then given a different treatment, the experimental class learning model SAVI, and grade control with conventional learning (direct). After learning is completed given postes, obtained postes with an average value of 76.83 experimental class and control class 66.87. Hypothesis test results using a different test (t-test) obtained t> t table so Ha is received, so that the results showed that there was a 15.67% influence learning model SAVI the learning outcomes of students of class VII in Learning Locally in the Junior songs Parulian 2 Medan